Phytochrome and temperature control of seed germination in Muntingia calabura L. (Elaeocarpaceae) - Leite, ITD; Takaki, M. (Inst Tecnologia Parana, 2001)
The temperature range of germination of seeds of Muntingia calabura L. was 15-35 degreesC and the optimum temperature at 35 degrees where more seeds germinated at short period. The fluence response curves demonstrated the involvement of phytochrome in the control of germination through the low fluence response. The effect of photoperiod showed that the species need long daily exposures to white light and that shade light inhibited completely seed germination, confirming as pioneer species that colonized only large gaps in the forest.
Keywords: seed germination; phytochrome; light; temperature; Muntingia calabura